2018
DOI: 10.3762/bjnano.9.115
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic modeling of tribological properties of Pd and Al nanoparticles on a graphene surface

Abstract: Background: The frictional properties of nanoparticles have been studied to gain insight into the fundamental origin of sliding friction. Results: Using molecular dynamics we investigate frictional properties of aluminum and palladium nanoparticles deposited on a graphene layer. We study the time evolution of the total momentum of the system, the total and potential energies, the temperature, the velocity and position of the center of mass, the dimensions of the nanoparticle, and the friction and substrate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition, working parameters which affect the friction property of nanoparticles, such as velocity [16], shape of nanoparticle [17], [18], temperature [19], [20] and normal load [21] have been well researched by the MD simulation. Hu et al [16] studied the friction behaviors of silicon dioxide and diamond nanoparticle with MD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, working parameters which affect the friction property of nanoparticles, such as velocity [16], shape of nanoparticle [17], [18], temperature [19], [20] and normal load [21] have been well researched by the MD simulation. Hu et al [16] studied the friction behaviors of silicon dioxide and diamond nanoparticle with MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the movement pattern of nanoparticles can be changed from sliding to rolling by tuning the nanoparticle shape. Khomenko et al [19] studied the friction properties of Pd and Al nanoparticles on a graphene surface and point out that the averaged friction force depends nearly linearly on the contact area and non-monotonously on the temperature.…”
Section: Introductionmentioning
confidence: 99%